"Rack 'em, Pack 'em and Stack 'em": Decarceration in an Age of Zero Tolerance. Issue 2 (1st November 2016) - Weatherburn, Don
Abstract: This article traces the recent history of prison population growth in Australia, discusses its causes, costs and benefits, and suggests ways in which the growth in Australian imprisonment rates may be contained or reversed without threat to public safety. Several options are discussed. They include abolishing short sentences, restoring discretion to the courts to set the relationship between the aggregate sentence and the non-parole period, giving Parole Boards greater discretion to deal with breaches of parole, reform of community corrections, and bail reform.